The Theme of Exile in Vladimir Vokolek's poetry (from late 1940s to early 1960s) - Filipi, Michaela (Bohemica Olomucensia, 2015)
The paper presents an analysis of Vladimir Vokolek's poems that were written between the late 1940s and early l960s. It focuses on the theme of exile. The word ``exile'' has two meanings: loss of home and alternative home. Vokolek's verses apply to both of them. The exile becomes characteristic for the word and subject situation within the period mentioned above. Our attention is paid primarily to the transformation of poet's aims.
Keywords: Vladimir Vokolek; theme of exile; loss of home; alternative home; Czech postwar poetry